Polish Language Sources of XIX - XX Centuries in Ukrainian Historical and Pedagogical Studies - Seiko, Nataliya (Pedagogical Discourse, 2013)
This paper presents an analysis of Polish-language scientific sources in Ukrainian historical and pedagogical studies. The article also reveals the place and role of Polish archival documents, materials of Polish periodicals of XIX – early XX century, memoirs and scientific works of XIX – XX centuries on history of education and culture, which were published in the Polish language in Ukraine and abroad, and also directories, dictionaries, bibliographies in the Polish language in Ukrainian history of pedagogics. The conclusion about the significance of Polish and Polish-language sources for carrying out the studies on the history of pedagogics is formulated.